2012
DOI: 10.1111/j.1745-4549.2012.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Demethoxycurcumin and Bisdemethoxycurcumin on Antioxidant Activity of Curcumin in Refined Sunflower Oil

Abstract: It is now agreed that food plays a major role in the maintenance of good health. The awareness of consumers about diet‐related health problems has increased. Hence, nowadays, preference is given to the natural food ingredients, which are expected to be safe and health promoting. Recently, many studies on health benefits associated with curcumin have been reported. In the present study, an attempt had been made to isolate curcumin from a mixture of curcuminoids by means of column chromatography technique. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[13] The antioxidant activity of curcumin was studied in refined sunflower oil (RSFO). [73] Antifibrotic Effect Punithavathi and coworkers [74] observed that oral administration of curcumin suppressed bleomycin-induced pulmonary fibrosis in rats.…”
Section: Subjectsmentioning
confidence: 99%
“…[13] The antioxidant activity of curcumin was studied in refined sunflower oil (RSFO). [73] Antifibrotic Effect Punithavathi and coworkers [74] observed that oral administration of curcumin suppressed bleomycin-induced pulmonary fibrosis in rats.…”
Section: Subjectsmentioning
confidence: 99%
“…Also, since they possess electron donating hydroxyl group in the aromatic ring and electron withdrawing carbonyl group in heptadienone moiety, structures (3) and (4) can be drawn respectively. The existence of structures (3) and (4) has already been proven by NMR data [14]. Structures 3 and 4 resemble the enol tautomer ( Figure 1).…”
Section: Proportion Of Keto and Enol Tautomers Of Curcuminoidsmentioning
confidence: 53%
“…Curcumin has higher pharmacological activity than bisde methoxycurcumin and demethoxycurcumin (Sandur et al 2007;Jayaprakasha et al 2006). However, the mixture of three curcuminoids has better activity compared only curcumin (Rege et al 2014).…”
Section: Introductionmentioning
confidence: 92%